2004
DOI: 10.1200/jco.2004.08.185
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Multiple Dose Levels of CCI-779, a Novel Mammalian Target of Rapamycin Kinase Inhibitor, in Patients With Advanced Refractory Renal Cell Carcinoma

Abstract: In patients with advanced RCC, CCI-779 showed antitumor activity and encouraging survival and was generally well tolerated over the three dose levels tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
510
2
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 904 publications
(547 citation statements)
references
References 39 publications
23
510
2
12
Order By: Relevance
“…This interpretation is strengthened by our observation that confluency dramatically affected phospho-RPS6 levels in WT8 cells. Alternatively, mTOR may be activated in only a subset of RCCs in agreement with the observed 7% response rate to CCI-779 (Atkins et al, 2004).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This interpretation is strengthened by our observation that confluency dramatically affected phospho-RPS6 levels in WT8 cells. Alternatively, mTOR may be activated in only a subset of RCCs in agreement with the observed 7% response rate to CCI-779 (Atkins et al, 2004).…”
Section: Discussionsupporting
confidence: 67%
“…Tuberous sclerosis mutant cells have an exaggerated HIFa response to hypoxia, which is blocked by treatment with rapamycin. A rapamycin prodrug, CCI-779 (Wyeth), has been examined as a single agent in RCC (Atkins et al, 2004). The response rate was low (7%) but included one complete response.…”
mentioning
confidence: 99%
“…Results have been reported from studies in metastatic breast (MBC), renal cell (RCC), 75 small cell lung, (SCLC), 76 endometrial carcinoma, 77 mantle cell lymphoma (MCL), 78 melanoma, 79 and glioblastoma multiforme (GBM). 80,81 The results of these studies are summarized in Table 2.…”
Section: Temsirolimus (Cci-779)mentioning
confidence: 99%
“…Temsirolimus (sirolimus 42-ester 2,2-bis hydroxymethyl propionic-acid; CCI-779) is a more water-soluble ester derivative of its parent compound sirolimus, selected for development as an anticancer agent based on its more favourable pharmaceutical characteristics and superior therapeutic index. Temsirolimus has already been tested in phase I and II trials with promising activity and good safety profile (Atkins et al, 2004;Baselga et al, 2004;Raymond et al, 2004;Chan et al, 2005). In phase I studies, rash and mucositis were dose-limiting, and other adverse events (AE) observed include eczematous reactions, dry skin, herpes-type lesions, mild myelosupression, hypercholesterolaemia and hypertriglyceridemia (Atkins et al, 2004;Baselga et al, 2004;Raymond et al, 2004).…”
mentioning
confidence: 99%